Measuring the Barriers to Adherence With Neurology Clinic Appointments for Children With Epilepsy: A Pilot Study. (26th April 2021) - Bailey, Jason; West, Melanie; Agarwal, Rajkumar; Kumar, Gogi
Introduction: Epilepsy is one of the most common neurological disorders in children. Missed appointments reflect missed opportunity to provide care for children with epilepsy. The objective of this study was to identify social determinants of health (SDH) and other factors associated with missed appointments in children with epilepsy and measure the relation between missed appointments and frequency of emergency room (ER) visits and inpatient admissions. Methods: This was a prospective study conducted in the neurology division at a level 4 epilepsy center. Children (0 to < 18 years of age) with a diagnosis of epilepsy were included and a semi-structured questionnaire was provided to the families. Patients with 2 or more missed neurology clinic appointments in the previous year ("study group", n = 36) were compared to those with 1 or zero missed appointments ("control group", n = 49). A comparison of the clinical characteristics, emergency room visits and hospitalizations in the past year as well as SDH was performed. Statistical analysis was performed using SPSS and p < 0.05 was considered significant. Results: The mean age, gender distribution and presence of medical refractoriness were comparable between the 2 groups. Families in the study group reported a higher likelihood of having to make special work arrangements for clinic appointments. Children in the study group were noted to have a significantly higher frequency of single mother households, presence of public insurance, father not graduating from high school and household income less than 50, 000 dollars. Within the preceding year, children in the study group were noted to have a higher frequency of visits to the emergency department as well as 6 times higher likelihood of inpatient hospitalization for seizures. Conclusions: Social determinants of health play an important role in determining adherence with neurology clinic visits in children with epilepsy. Children with more missed appointments are likely to have a higher frequency of visits to the emergency department as well as a higher incidence of hospitalization for seizures. Identification of high-risk families and implementation of early interventions may improve adherence to office visits and decrease emergency room visits and hospitalization for seizures.